Pengaruh tingkat yang berbeda dari substitusi tepung ikan dengan tepung darah pada pakan ikan mas Cyprinus carpio L. dalam wadah terkontrol - Wungkana, Vike V.; Mokolensang, Jeffrie F.; Watung, Juliaan Ch.; Lumenta, Cyska; Salindeho, Indra R. N.; Wantasen, Adnan S.; Manu, Lusia (Universitas Sam Ratulangi, 2022)
The purpose of this study was to determine the feasibility using of blood meal on the growth rate and nutrient utilization of C. carpio L., as well as feeding with various levels of blood meal inclusion. The results showed that the absolute growth of common carp in treatment 1 with a combination was 10% higher than the other treatments. The daily growth rate of common carp in treatment 1 (1,8% / day) was higher than other treatments. Likewise, with the feed change value, treatment 1 showed significantly different from other treatments. The combination of fish meal and blood meal showed significantly different results from the results of statistical tests